2018
DOI: 10.3847/1538-3881/aac6cd
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Neptunian Objects Transiently Stuck in Neptune’s Mean-motion Resonances: Numerical Simulations of the Current Population

Abstract: A substantial fraction of our solar system's trans-Neptunian objects (TNOs) are in mean-motion resonance with Neptune. Many of these objects were likely caught into resonances by planetary migration-either smooth or stochastic-approximately 4 Gyr ago. Some, however, gravitationally scattered off of Neptune and became transiently stuck in more recent events. Here we use numerical simulations to predict the number of transiently stuck objects, captured from the current actively scattering population, that occupy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 35 publications
(75 reference statements)
4
61
0
Order By: Relevance
“…In the specific case of the resonance 1:2, the closest resonance with some, though tiny, dynamical traces seems to be 15:29. Yu et al (2018) performed numerical integrations of particles with 30 < a < 100 au looking for captures in MMRs and they obtained a very illustrative map of captures for resonances k p :k (q:p using their notation) that shows that the efficiency of captures drops substantially for k p > 13 in very good agreement with our results. It is worth mentioning that Chambers (1997) studied the credibility of exterior MMRs with Jupiter and concluded that for high k/k p ratios the binding energies of the comets to the Sun are not large enough to overcome the planetary perturbations and the resonances cannot work.…”
Section: On the Existence Of High K P :K Resonancessupporting
confidence: 80%
“…In the specific case of the resonance 1:2, the closest resonance with some, though tiny, dynamical traces seems to be 15:29. Yu et al (2018) performed numerical integrations of particles with 30 < a < 100 au looking for captures in MMRs and they obtained a very illustrative map of captures for resonances k p :k (q:p using their notation) that shows that the efficiency of captures drops substantially for k p > 13 in very good agreement with our results. It is worth mentioning that Chambers (1997) studied the credibility of exterior MMRs with Jupiter and concluded that for high k/k p ratios the binding energies of the comets to the Sun are not large enough to overcome the planetary perturbations and the resonances cannot work.…”
Section: On the Existence Of High K P :K Resonancessupporting
confidence: 80%
“…The resonance sticking mechanism was first noticed by Duncan and Levison (1997) and since then is has been studied by a number of authors. In particular, it was found for objects in Neptune encountering orbits (scattered TNOs) (Lykawka and Mukai 2007;Yu et al 2018), and in the temporarily capture of Uranian and Neptune Trojans from the dynamical evolution of Centaurs (Alexandersen et al 2013). We note several resonance captures in the whole evolution with a tendency of GPCs to be captured into MMR with Neptune: 1:1, 3:2, 2:1 and 3:1 and 5:2.…”
Section: Dynamical Evolution Of Observed Gpcmentioning
confidence: 58%
“…In particular, Lykawka and Mukai (2007) found that evolution of scattered TNOs is described by multiple temporary resonance sticking and continuous scattering by Neptune and that this mechanism is relevant mostly at a < 250 au, consistent with our result. Yu et al (2018) predicted that the current transient-sticking population comprises 40% of the total transiently stuck + scattering TNOs, and therefore is a very important mechanism in the SD zone.…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…RTNOs show dynamical characteristics (e.g., inclination distribution) different from those of the classical Kuiper belt, but may be connected to the scattered disk population (Gomes et al 2008), objects on high eccentricity orbits with perihelia beyond Neptune, and semi-major axes beyond the 2:1 resonance. Recent studies (Yu et al 2018) indicate that a significant fraction of all scattered objects are transiently stuck in mean motion resonances, suggesting that these objects originated from the same single population.…”
Section: Introductionmentioning
confidence: 99%